1994
DOI: 10.1111/j.1349-7006.1994.tb02396.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Renal Cell Tumors in Long‐Evans Cinnamon Rats

Abstract: Neoplastic lesions of the kidneys in untreated Long‐Evans Cinnamon (LEC) rats of 57–118 weeks old (85 males and 34 females) and male F344 rats of 64–93 weeks old (59 males) were examined histologically. The incidences of renal cell tumors in male and female LEC rats were 6/80 (8%) in weeks 57–65, 3/19 (16%) in weeks 66–75, 3/8 (38%) in weeks 76–105 and 7/12 (58%) in weeks 106–118. Of these tumors, 13 were microscopic adenomas and 7 were renal cell carcinomas. The copper content of the kidneys was about three t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Increased Cu levels [36] and tissue damage [35] were shown in LEC rat kidneys. It has also been reported that the incidence of renal cell tumors increases with advance of age in LEC rats [9,12].…”
Section: Introductionmentioning
confidence: 81%
“…Increased Cu levels [36] and tissue damage [35] were shown in LEC rat kidneys. It has also been reported that the incidence of renal cell tumors increases with advance of age in LEC rats [9,12].…”
Section: Introductionmentioning
confidence: 81%
“…In the present study, we demonstrated that, 1) hepatocellular tumors developed spontaneously in WKAH.C-Atp7b rats, but the incidence was slightly lower than that of LEC rats, 2) LEC rats were more susceptible to DEN than WKAH.C-Atp7b rats in the medium-term bioassay, but progression of the preneoplastic foci to hepatocellular tumors in LEC rats was worse than that in WKAH.CAtp7b and WKAH rats as shown in the long-term carcinogenicity study, 3) incidences of spontaneous liver tumors in LEC, WKAH.C-Atp7b and WKAH rats correlated with hepatic copper and iron concentrations, and 4) spontane- ous renal cell tumors, which are common in aged LEC rats, 10) were not found in WKAH.C-Atp7b rats, though LEC and WKAH.C-Atp7b rats, both of which have high renal copper accumulation, were more susceptible to DEN-induced renal carcinogenesis than WKAH rats with low renal copper concentration. These data suggest that the susceptibility of LEC rats to liver and kidney carcinogenesis could be explained by excess copper and/or iron accumulation in these organs.…”
Section: Discussionmentioning
confidence: 99%
“…In LEC rats of over one year old, tumors of the liver and kidney develop spontaneously, and parenchymal cells in both the liver and kidney accumulate copper. 9,10) The incidence of hepatocellular tumors in LEC rats was 15% in males of 51-60 weeks old, all being adenomas, and the incidence of hepatocellular carcinomas was 50% even in males of 111-120 weeks old. In addition, copper chelating agents (D-penicillamine and trientine dihydrochloride) inhibited the development of liver tumors as well as hepatitis of LEC rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have reported that renal cell tumors develop spontaneously in LEC rats. 10) In the present study, we examined preneoplastic and neoplastic lesions of the kidneys in rats of 51-120 weeks old, and the changes in renal copper and iron concentrations of LEC and F344 rats of 6-106 weeks old. We also investigated the effect of D-penicillamine on spontaneous renal carcinogenesis.…”
mentioning
confidence: 99%